Topophysis and Growth Regulators Effects on Buds and Zygotic Embryos Regeneration of African Bush Mango Tree Cultured In vitro (2022). - AGBIDINOUKOUN, ARNAUD; Noumon, André-Tudal; QUENUM, FLORENT JEAN-BAPTISTE (My University, 2022)
Background: African bush mango tree is an important fruit plant with high nutritional, medicinal, and commercial values. However, its seedling system remained a deep understanding. This study aimed to evaluate the effect of topophysis and growth regulators on the reactivity of different types of buds and zygotic embryos of wild mango. Methodology: Ripe fruits from two local varieties (Wossro and Sissro) were pulped. The nuts were extracted and dried for one week under greenhouse. Zygotic embryos were excised from nuts and disinfected with the bleach solution (NaClO 10% with 8% active chloride) for 10 min following by three successive rinsing using sterilized water. The second set of nuts was cultivated for under greenhouse in the polybags containing the sand. One month later, buds from different positions (apical, axillary and cotyledonary) were excised and disinfected with NaClO 10% for 10 min follow by the immersion in a mercuric chloride 0.1% added with two drops of Tween 20 especially for axillary and cotyledonary buds for 5 min while 0.01% of mercuric chloride was used for apical buds. The explants were cultured on ¼MS and ½WPM media supplemented with BAP, KIN at different concentrations (0.2 mg/L and 3.5 mg/L respectively) and NAA (0.05 mg/L). Results: The best sprouting rate was obtained with the variety Wossro which showed a high bud break rate (26.47%) against (9.88%) for the variety Sissro. The topophysis significantly influenced the response of the buds in tissue culture. 24.48% of axillary buds were sprouted on ¼ MS medium + 3.5 mg/L BAP+ 0.05mg/L NAA. The in vitro germination of embryos was significantly (p≤ 0.05) influenced by the genotype of the variety. 50.76% of buds were germinated for Wossro while 18.32% were germinated for Sissro. ¼ MS + 0.2 mg/L KIN has significant influenced the plants growth and development. Implication: The findings will help to improve the regeneration rate and plantlets production of African bush mango tree.
Keywords: Irvingia gabonensis; topophysis; In vitro regeneration; bud morphogenic capacity; zygotic embryos; culture media